Laporan Kasus: Diabetes Melitus tipe 2 disertai Obesitas dengan Konsumsi Rebusan Buah Pare - Kamaruddin, M Yusril; Makmun, Armanto (Indonesian Journal of Health, 2024)
Diabetes mellitus requires continuous medical care as it is a chronic condition. Type 2 diabetes mellitus is the most common type and is influenced by many variables, including environmental and genetic factors. Due to urbanization, people's lifestyles have changed, shifting from healthy eating to fast food consumption. Compared to individuals with normal weight, obese individuals have a four times higher risk of type 2 diabetes. To control blood glucose, both pharmacological and non-pharmacological treatments are necessary in the management of diabetes mellitus. Momordica Charantia, or bitter melon, is a natural plant that can be used as an alternative treatment for diabetes mellitus. Bitter melon has long been used as a medicinal remedy and possesses hypoglycemic properties, according to literature studies. The chemical compound charantin found in bitter melon exhibits properties similar to insulin, helping to reduce blood glucose levels. These studies indicate that pharmacological treatment and the incorporation of bitter melon as a non-pharmacological therapy can lower blood sugar levels in individuals with diabetes mellitus.